2020
DOI: 10.3390/plants9020150
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Effects on the Plasma Membrane Produced by Addition of Fumonisin B1 to Maize Embryos

Abstract: Fumonisin B1 is a mycotoxin produced by Fusarium verticillioides that modifies the membrane properties from animal cells and inhibits complex sphingolipids synthesis through the inhibition of ceramide synthase. The aim of this work was to determine the effect of Fumonisin B1 on the plant plasma membrane when the mycotoxin was added to germinating maize embryos. Fumonisin B1 addition to the embryos diminished plasma membrane fluidity, increased electrolyte leakage, caused a 7-fold increase of sphinganine and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…FB 1 also acts as a sphingolipid by becoming inserted into membranes due to its amphipathic nature, thereby decreasing membrane fluidity (Figure 5E) (Mahfoud et al, 2002; Gutierrez‐Najera et al, 2005). In vivo treatment of maize embryos with FB 1 indicated that the toxin first inhibits the ceramide synthase, and this action will subsequently accumulate sphinganine in the PM, changing the fluidity and thereby inhibiting PM H + ‐ATPase activity (Gutierrez‐Najera et al, 2020). The toxin must therefore have multiple functions since it changed the activity of the pump differently in vitro compared to in vivo .…”
Section: Membrane‐affecting Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…FB 1 also acts as a sphingolipid by becoming inserted into membranes due to its amphipathic nature, thereby decreasing membrane fluidity (Figure 5E) (Mahfoud et al, 2002; Gutierrez‐Najera et al, 2005). In vivo treatment of maize embryos with FB 1 indicated that the toxin first inhibits the ceramide synthase, and this action will subsequently accumulate sphinganine in the PM, changing the fluidity and thereby inhibiting PM H + ‐ATPase activity (Gutierrez‐Najera et al, 2020). The toxin must therefore have multiple functions since it changed the activity of the pump differently in vitro compared to in vivo .…”
Section: Membrane‐affecting Compoundsmentioning
confidence: 99%
“…Fumonisin B 1 Fumonisin B 1 (FB 1 ) is produced by various Fusarium species (Table 2, Figure 3) that cause root, stalk, and ear rot in maize (Z. mays) (Leslie, 1996). FB 1 potentially inhibits the activity of membrane-localized enzymes, such as the sphinganine Nacyltransferase, as FB 1 treatment led to the accumulation of sphinganine in the PM (Abbas et al, 1994;Gutierrez-Najera et al, 2020). The inhibitory effect of FB 1 on maize PM H + -ATPases has also been investigated (Gutierrez-Najera et al, 2005).…”
Section: Membrane-affecting Compoundsmentioning
confidence: 99%
“…It is well known that FB1 modifies the "SphingoLipid rheostat. " Sphingolipids, such as Cer and S1P, facilitate EV biogenesis, promoting vesicle buddings inside MVB and ectosomes (Nora et al, 2020). Our TEM results demonstrate the existence of both types of EV.…”
Section: Discussionmentioning
confidence: 54%
“…Our TEM results demonstrate the existence of both types of EV. EV is known as cell-to-cell communication mediators due to their ability to transfer biomolecules among cells and to influence the extracellular microenvironment via regulation of critical nutrients (Nora et al, 2020). F. verticillioides needs to be considered as a producing ready-to-use SM factory and could be interpreted as an armed soldier, ready to shoot for maintaining its species survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation